The Shadow of Tower of Babel on Synodal Authority - Thelakat, Paul (Asian Horizons, 2020)
Synodality is a mode of being the church, interpreted in eight hermeneutical circles. The authority could be compared to writing a novel from dialogic orientation of a word among other words creating new and significant artistic potential in discourse. Every concrete utterance of a speaking subject is, accordingly, the locus in which centrifugal as well as centripetal forces confront each other. The processes of centralisation and decentralisation, of unification and disunification, intersect in the utterance. Every utterance is an active participant in such speech diversity. The freedom of people of God involve “much debate” but also much attention, which is prayer. The leader has to become an exiled author with the power of persuasion in the mystical body becoming a confessing church with the word of God becoming event of communion. The power of a Synod is the power of the holy language, which is dialogue.